More than medicine : a history of the feminist women's health movement - Nelson, Jennifer, 1967- (New York University Press, 2015)
"Years before discussing social and racial disparities in health became fashionable, some feminists were insisting that women's health and reproductive freedom could not be achieved without addressing issues such as poverty, nutrition, and economic inequality. In More Than Medicine, Jennifer Nelson uses exciting new primary research to trace the history of the movement for reproductive justice, from the 1960s to the present. She skillfully tells the story of the activists who fought to broaden health reform beyond medical care, and to broaden the feminist movement beyond abortion rights. Everyone interested in the past, present, and future of health reform, women's rights, and human rights should read this book."--Beatrix Hoffman, Northern Illinois University